A brief history of crystalloids: the origin of the controversy - Fernández-Sarmiento, Jaime; Casas-Certain, Carolina; Ferro-Jackaman, Sarah; Solano-Vargas, Fabian H.; Domínguez-Rojas, Jesús Ángel; Pilar-Orive, Francisco Javier (Frontiers in Pediatrics, 2023)
Fluid resuscitation with crystalloids has been used in humans for more than 100 years. In patients with trauma, sepsis or shock of any etiology, they can help modify the clinical course of the illness. However, these solutions are medications which are not side-effect free. Recently, they have been questioned in terms of quantity (fluid overload) and their composition. The most frequently used crystalloids, both in high and low-income countries, are 0.9% normal saline (NS) and Ringer's lactate. The first descriptions of the use of sodium and water solutions in humans date from the cholera epidemic which spread throughout Europe in 1831. The composition of the fluids used by medical pioneers at that time differs greatly from the 0.9% NS used routinely today. The term "physiological solution" referred to fluids which did not cause red blood cell hemolysis in amphibians in in vitro studies years later. 0.9% NS has an acid pH, a more than 40% higher chloride concentration than plasma and a strong ion difference of zero, leading many researchers to consider it an unbalanced solution. In many observational studies and clinical trials, this 0.9% NS composition has been associated with multiple microcirculation and immune response complications, acute kidney injury, and worse clinical outcomes. Ringer´s lactate has less sodium than plasma, as well as other electrolytes which can cause problems in patients with traumatic brain injury. This review provides a brief summary of the most important historical aspects of the origin of the most frequently used intravenous crystalloids today.